Rhetoric In Advertising - Vu, Doan (VNU Journal of Science: Policy and Management Studies, 2017)
Advertising mobilizes many methods relevant to three fundamental elements of Rhetoric such as Ethos, Pathos and Logos by using, for example Rhetorical Figures such as special images, unusual words, and arrangement of informations leading to desirable deduction and strong emotion. Methods using images are more efficient than traditional ones using words. They are known as Visual rhetoric.  In television, these methods prove a good combination of word and image for high efficiency.